Cloud computing three-factor user authentication framework and protocols for telecare medical information system - Siddiqui, Zeeshan (2015)
The Telecare Medical Information System (TMIS) provides a set of different medical services to patients and medical practitioners. The patients and medical practitioners can easily connect to the services remotely from their own premises, whereas, medical practitioners can observe the wellbeing of their patients remotely. There are several studies carried out to securely authenticate a remote user to use the TMIS facility more securely. Researchers have proposed several Smartcard authentication protocols for TMIS systems while addressing a number of authentication attacks along with performance issues. However, current TMIS authentication mechanism is highly vulnerable to a number of authentication attacks. Therefore lacks a completely secure, authentic and validated authentication framework. The primary objective of this study is to propose a secure Cloud Computing Three Factor user authentication framework and protocols for TMIS facility. To accomplish this, the authentication framework is supported by TMIS Service Cataloguing and Initialization protocol and TMIS Service Stimulation and Reset Protocol. The framework and protocols are verified using Burrows Abadi Needham logic standard and validated using Scyther authentication testing. The performance is judged using Profiler Analysis. The security and performance analysis has proved that the design and developed framework and protocols are highly resilient to classical and modern authentication attacks while maintaining higher level of security during the complete authentication process. The authentication analysis has proved that the proposed work has delivered a verifiable and validated security framework and protocols for TMIS facility